Comparative aspects of canine and human inflammatory breast cancer - Raposo, T.P.; Arias-Pulido, Hugo; Chaher, Nabila; Fiering, Steven N.; Argyle, David J.; Prada, Justina; Pires, Isabel; Queiroga, Felisbina Luísa (Elsevier, 2017)
Inflammatory breast cancer (IBC) in humans is the most aggressive form of mammary gland cancer and shares clinical, pathologic, and molecular patterns of disease with canine inflammatory mammary carcinoma (CIMC). Despite the use of multimodal therapeutic approaches, including targeted therapies, the prognosis for IBC/CIMC remains poor. The aim of this review is to critically analyze IBC and CIMC in terms of biology and clinical features. While rodent cancer models have formed the basis of our understanding of cancer biology, the translation of this knowledge into improved outcomes has been limited. However, it is possible that a comparative “one health” approach to research, using a natural canine model of the disease, may help advance our knowledge on the biology of the disease. This will translate into better clinical outcomes for both species. We propose that CIMC has the potential to be a useful model for developing and testing novel therapies for IBC. Further, this strategy could significantly improve and accelerate the design and establishment of new clinical trials to identify novel and improved therapies for this devastating disease in a more predictable way.